Spine epidural and sacroiliac joints injections – when and how to perform. Issue 5 (May 2015) - D'Orazio, Federico; Gregori, Lorenzo Maria; Gallucci, Massimo
Highlights: Image guided interventions focused to administer drugs inside the epidural space are effective in reducing the perceived spinal pain, but their efficacy seems to be limited in time. To treat spinal pain with image guided interventions is safe and repeatable. Sacroiliac dysfunction is a common cause of sciatica-like pain which can be treated with CT-guided interventions (both steroids and pulsed RF denervation). Abstract: Objectives: To review the state-of-the-art of image – guided techniques used to treat painful syndromes of the lower back, their indications, how they should be performed, their related risks and the expected results. Methods: We describe the actual standards about image-guided infiltrative therapies both on spine and on sacroiliac joints. Results: Both spinal epidural and sacroiliac injections appear useful in a large percentage of treated patients to get control of the perceived pain. Performing these therapies under CT or fluoroscopic guidance is the best and safest way to obtain satisfactory results because it is possible to target the use of drugs directly to the involved painful structures. Conclusions: Image-guided injections of the epidural space and of the sacroiliac joints are effective techniques for the treatment of pain; their effectiveness is sometimes not lasting for long periods of time but considering the low associated risk when performed by trained personnel, they can be easily repeated.